Synthesis, characterization and applications of palm fatty acid functionalized magnetic nanoparticles as new adsorbents / Siti Khalijah Mahmad Rozi - Siti Khalijah , Mahmad Rozi (2018)
In this study, three new adsorbents were synthesized, free fatty acids from hydrolysis of triacylglycerol of palm cooking oil functionalized magnetic nanoparticles (MNP@FFAs-PCO), free fatty acids from waste palm cooking oil functionalized magnetic nanoparticles (MNP@FFAs-WPCO) and free fatty acids from waste palm cooking oil functionalized magnetic nanoparticles immobilized on the surface of the graphene oxide (MNP@FFAs-WPCO-GO) for the preconcentration and remediation of organic pollutants from various sample matrices. The structure of MNP@FFAs-PCO and MNP@FFAs-WPCO were characterized by XRD, TEM, FT-IR, FESEM, VSM, EDX, BET, TGA analyses and water contact angle measurement. The obtained results prove the successful synthesis of these adsorbents. Furthermore, it was also revealed that MNP@FFAs-WPCO has a larger surface area and higher hydrophobicity compared to MNP@FFAs-PCO. The synthesized MNP@FFAs-PCO and MNP@FFAs-WPCO were used as adsorbent for magnetic solid phase extraction (MSPE) of polycyclic aromatic hydrocarbons (PAHs) and for the removal of oil from aqueous media. The MNP@FFAs-PCO and MNP@FFAs-WPCO showed a low limit of detection (LOD) ranging from 0.01 to 0.05 ng mL-1 and 0.001 to 0.05 ng mL-1, respectively and limit of quantification (LOQ) in the range of 0.03-0.16 ng mL-1 and 0.004-0.2 ng mL-1, respectively. The application of MNP@FFAs-PCO and MNP@FFAs-WPCO were successfully studied on the leachate and sludge from a landfill site. The MNP@FFAs-PCO recorded good recovery (81.1-119.3%) with satisfactory precision (%RSD: 3.1–13.6) while MNP@FFAs-WPCO showed satisfactory recovery (72.3–119.9%) with acceptable precision (%RSD: 4.8–11.8). The MNP@FFAs-PCO and MNP@FFAs-WPCO were also found to be able to adsorb 3.50 times and 4.31 times of oil higher than their own weight, respectively. In this study, it was found that MNP@FFAs-WPCO showed an excellent MSPE performance as it provided lower LOD for all selected PAHs and good oil sorption capacity in comparison with the performance MNP@FFAs-PCO. The third adsorbent, MNP@FFAs-WPCO-GO was characterized by FT-IR, XRD, FESEM, TGA, TEM, VSM and EDX analyses to confirm its structure. It was successfully applied as a MSPE adsorbent for simultaneous separation of selected PAHs and phthalate esters (PAEs). It has good performance with low LODs ranging from 0.02 – 0.93 ng mL-1 for PAHs and 0.56 – 0.97 ng mL-1 for PAEs with LOQs in the range of 0.07 to 3.10 ng mL-1 for PAHs and 1.86 to 3.20 ng mL-1 for PAEs. The MNP@FFAs-WPCO-GO was successfully studied on apple, cabbage and landfill sludge samples. High recoveries (81.5 – 118.2% for PAEs) and (86.7 – 118.8% for PAHs) with satisfactory precision (%RSD: 2.1 to 9.9 for PAEs, 1.5 to 11.0 for PAHs) were obtained.